Stock photos of the Medford/Somerville campus, including the jumbo statue and the cannon at night and the library roof. Photo 003 - Sobecki, Nicki (Tufts Archival Research Center, 2008)
Stock photos of the Medford/Somerville campus, including the jumbo statue and the cannon at night and the library roof.